Inovasi Manajemen Perencanaan Kepala Sekolah dalam Meningkatkan Mutu Pendidikan - M. Jali (Kependidikan Islam Fakultas Agama Islam, 2023)
This research discusses the principal's management in improving the quality of education at Miftahul Jannah Segedong Middle School. The aim of this research is to find out how the principal plans and implements in improving the quality of education at Miftahul Jannah Segedong Middle School. This research is descriptive qualitative in nature using interviews, observation and documentation as data collection. Analyzing data by compiling data, managing data, then describing it systematically. The result of the principal's management in improving the quality of education at Miftahul Jannah Segedong Middle School is that the principal holds a meeting to plan the annual program, then the results of the meeting will be socialized to teachers, students, parents and the school committee, then improving the quality of the principal's activities such as: recitation, muhadarah by presenting a ustadz, practicing prayers, then familiarizing students with the Al-Qur'an by carrying out activities one verse a day which are carried out in turns and reading every morning assembly. Then, in the learning process, the principal suggests that teachers use varied methods, be disciplined in class schedules, have work accountability, deliberation in deciding a problem, openness in determining costs and development money.